Experimental studies on effects at micro-structuring of highly reflecting metals using nano- and picosecond-lasers - Reg, Yvonne; Kaegeler, Christian; Schmidt, Michael (Physics Procedia, 2010)
Microstructuring of highly reflective metals was performed using high-power nanosecond- and picosecond-laser beam sources. This contribution mainly focuses on the ablation depth, achievable sidewall inclination angles and the ablation quality. Single- and multilayer structures with varying width and depth were generated to analyse the interdependency of the resulting ablation quality with the processing parameters and strategies used. As results, optimized strategies to generate different geometrical structures with specified qualities and processing times are proposed. In addition, an effect occurring at ps-multilayer ablation, which was up to now only described theoretically, will be presented.
Created from Fastlane, Scopus look-up
Keywords: Laser material processing; Laser-based; Photonic technologies; Processes; Ultrashort pulse lasers